Cornea eye care coverage based on geographic distribution and population demographics in the United States - Riya H. Patel; David Mothy; Hassaam S. Choudhry; Aliya Grinberg; Jayant Bhasin; Mohammad H. Dastjerdi (AJO International)
Purpose: To correlate the geographic distribution of cornea-specializing ophthalmologists with United States population demographics and identify communities with gaps in cornea care access. Design: Cross-sectional analysis Methods: In June 2024, office addresses of cornea ophthalmologists obtained from the Academy of Ophthalmology (AAO) public database and Google searches were geocoded using Esri ArcGIS Pro. Geographic distribution of cornea ophthalmologists within the United States compared to US county-level population demographics, such as county median incomes, educational attainment rates, poverty rates, and health insurance coverage rates. Independent samples t-tests were used for statistical analysis. Results: 1665 cornea ophthalmologists’ office addresses were identified. 85.6 % (n = 2688) of US counties had no practicing cornea ophthalmologists whereas 14.3 % (n = 447) of US counties had at least one cornea ophthalmologist. There was an average of 5.02 cornea ophthalmologists per million people throughout the United States. When correlated with population demographics, counties with at least one cornea ophthalmologist had greater median income [$77,444], educational attainment rates [35.5 %], and health insurance coverage rates [98.6 %] compared to the median household annual income [$60,872], educational attainment rates [21.4 %], and health insurance coverage rates [97.5 %] of counties with no cornea ophthalmologists (p < 0.001). Additionally, counties with at least one cornea ophthalmologist had lower poverty rates [12.0 %] compared to counties with no cornea ophthalmologists [14.2 %] (p < 0.001). Conclusions: Geographic disparities in cornea care access are pronounced in low socioeconomic counties. Addressing these issues is crucial for equitable eye care.